In-situ Iberian pig carcass classification using a micro-electro-mechanical system (MEMS)-based near infrared (NIR) spectrometer. - Zamora-Rojas, E.; Pérez-Marín, D.; De Pedro-Sanz, E.; Guerrero-Ginel, J. E.; Garrido-Varo, A. (Meat science, 2012)
Iberian pig (IP) products are gourmet foods highly appreciated at international markets, reaching high prices, because of its exquisite flavors. At present, there aren't practical and affordable analytical methods which can authenticate every single piece put on the market. This paper reports on the performance of a handheld micro-electro-mechanical system (MEMS)-based spectrometer (1600-2400nm) for authentication-classification of individual IP carcasses into different commercial categories. Performance (accuracy and instrumental design) of the instrument was compared with that of high-resolution NIRS monochromators (400-2500nm). A total of 300 carcasses of IPs raised under different feeding regimes ("Acorn", "Recebo" and "Feed") were analyzed in three modes (intact fat in the carcass, skin-free subcutaneous fat samples and melted fat samples). The best classification results for the MEMS instrument were: 93.9% "Acorn" carcasses correctly classified, 96.4% "Feed" and 60.6% "Recebo", respectively. Evaluation of model performance confirmed the suitability of the handheld device for individual, fast, non-destructive, low-cost analysis of IP carcasses on the slaughterhouse line.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 22075264
Keywords: Authentication; Feeding regime; Iberian pi; In-situ analysis; MEMS device; NIRS